Media Baru dan Fenomena Komunikasi Politik pada Pemilukada di Provinsi Banten 2011 - Afdal Makkuraga Putra (Universitas Multimedia Nusantara, 2011)
Political system in Indonesia after New Order regime has entered into a new phase, which is both fundamentally and practically different. With the growth of freedom of expression and the rise of information and communication technology (ICT), the use and practices of political communication is also striking a fair balance, two-ways direction, no longer dominated by government-only apparatuses. The use of internet and New Media in political communication realm has been pioneered since 1997, and has been growing ever since, thanks to the new practices of local election (Pilkada). This paper will address firstly, the theoretical framework of political communication in e-Democracy, and secondly, the application of New Media (website, blog, and social media sites) in local-based political communication, namely Pilkada in Banten at October 23, 2011. Having analysed the phenomenon in question, a surprising result appears. Even though all candidates of Governor and Deputy Governor of recent Pilkada Banten have used New Media as their communication and campaign media, nevertheless the interactivity factor embedded within those